Nuclear transcriptional regulation by mitochondrial-encoded MOTS-c - Lee, Changhan (Molecular and Cellular Oncology, 2019)
Cellular stress response is coordinated through the communication between mitochondria and the nucleus. However, whereas mitochondria are regulated by nuclear-encoded proteins, the nucleus was considered ungoverned by mitochondrial-encoded factors. We recently reported that a mitochondrial-encoded peptide directly regulates the nuclear genome upon cellular stress, indicating an integrated bi-genomic cross-communication mechanism.
Keywords: adaptive gene expression; homeostasis; MDPs; Mitochondria; mitochondrial-derived peptides; mitonuclear communication; MOTS-c; nuclear translocation; stress resistance; stress response